2017
DOI: 10.11646/phytotaxa.321.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Do we have different varieties in Acer velutinum (Sapindaceae): Morphological and molecular studies

Abstract: The genus Acer L. has about 156 species which are distributed in Asia, Europe, Northern Africa and North America. The species of Acer show extensive morphological and molecular diversity and the species that co-occur may hybridize; therefore, sometimes the species delimitation turns out to be difficult. Eight Acer (maple) species have been reported in Iran. The velvet maple—Acer velutinum Boiss (1846: 28)—is one of the largest maples in the world and the most frequent maple species in Iran. Morphologically spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…In a similar study carried on the sympatric varieties of Acer velutinum in north of Iran, the observed genetic variability was reported due to the high gene flow or the introgression between these varieties with high leaf morphological diversity (Siahkolaee et al 2017).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a similar study carried on the sympatric varieties of Acer velutinum in north of Iran, the observed genetic variability was reported due to the high gene flow or the introgression between these varieties with high leaf morphological diversity (Siahkolaee et al 2017).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, DNA sequences like ITS (Internal transcribed spacer) and chloroplast DNA have been used in determining intraspecific variation in Acer species like A. pictum Thunb., A. velutinum Boiss., and A. campestre L. (Grimm and Thomas 2014;Siahkolaee et al 2017). Ideally, species should not be proposed or rejected solely based on descriptive (non-numeric) morphology; any taxonomic reassessment should be complemented by genetic evidence (diagnostic sequences, DNA fingerprinting, and population-genetic analyses) (Grimm and Thomas 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Species identification and differentiation is an important task for systematic and evolutionary studies. This may be difficult in the genera with overlapping morphological characters among the species, and in those genera that encounter inter-specific hybridization as well as ancient-historic introgression events (SIAHKOLAEE et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity is an important element in the survival of population, because it has a positive influence on the adaptation of species in the presence of fluctuating biological and abiotic factors (Vrijenhoek 1994). ISSR (Inter-simple sequence repeats) molecular markers are stable, highly reproducible, easy to work and are known to be useful in various biological investigations such as, species delimitation, genetic diversity analysis, population structure, breeding programs and conservation management (Shahi-Gharahlar et al 2011;Sheidai et al 2014;Koohdar et al 2015;Minaeifar et al 2016;Nikzat-Siahkolaee et al 2017;Tabaripour et al 2018 ).There are many studies which have been mainly focused on the taxonomy, phylogeny, nutlet micromorphology, cytology, anatomy, trichome and pollen morphology of Lamium species (Mill 1982;Mennema 1989;Abu-Asab and Cantino 1994;Özdemir 2009, 2011;Bendiksby et al 2011a, b;Celep et al 2011Celep et al , 2014Krawczyk et al 2013Krawczyk et al , 2014Atalaya et al 2016 a, b). However, genetic diversity of Lamium species have been reported in only a few studies (Wąsowicz et al 2011;Stojanova et al 2013;Azimishad et al 2018), also genetic structure, ecological adaptation, and intra-and inter-specific differentiation along with morphometric studies on Lamium of Iran have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%